Modern happiness. Venice in Vienna and transnational reproductions of pleasure - Wąsik-Linder, Monika (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
This article explores the history of the amusement park 'Venice in Vienna',founded by theatre entrepreneur Gabor Steiner in 1895 in Vienna's Leopoldstadtdistrict. Steiner's replica of Venice was an improved and expanded version of similarreplicas being built in other European cities at the time. In the article, theViennese amusement park is presented as an example of a cultural imaginariumwith a transnational character. The performative practice of the appropriation ofVenice in the context of the emerging entertainment culture in the metropolisesof the early 20th century is also reflected upon.